2001
DOI: 10.1086/320598
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Inheritance of Sialuria, an Inborn Error of Feedback Inhibition

Abstract: "French type" sialuria, a presumably dominant disorder that, until now, had been documented in only five patients, manifests with mildly coarse facies, slight motor delay, and urinary excretion of large quantities (>1 g/d) of free N-acetylneuraminic acid (NeuAc). The basic defect consists of the very rare occurrence of failed feedback inhibition of a rate-limiting enzyme, in this case uridinediphosphate-N-acetylglucosamine (UDP-GlcNAc) 2-epimerase, by a downstream product, in this case cytidine monophosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…More generally, deficits in one of the individual enzymes that reside in the lysosome also may cause stuttering or similar disorders. Speech deficits have been reported in other lysosomal storage diseases, including Tay-Sachs disease, Salla disease, and sialuria (56,60,82,99). For example, in patients with late-onset Tay-Sachs disease, stuttering has been suggested to be an early disease marker, presenting earlier than other symptoms such as muscle weakness, gait disturbance, or psychiatric disturbances (82).…”
Section: Genetic Linkage Studies Of Stutteringmentioning
confidence: 99%
“…More generally, deficits in one of the individual enzymes that reside in the lysosome also may cause stuttering or similar disorders. Speech deficits have been reported in other lysosomal storage diseases, including Tay-Sachs disease, Salla disease, and sialuria (56,60,82,99). For example, in patients with late-onset Tay-Sachs disease, stuttering has been suggested to be an early disease marker, presenting earlier than other symptoms such as muscle weakness, gait disturbance, or psychiatric disturbances (82).…”
Section: Genetic Linkage Studies Of Stutteringmentioning
confidence: 99%
“…This GNE gene has been known to be related to a rare autosomal dominantly inherited disorder, sialuria "French type" [12]. Three patients had heterozygous mutations (R266W, R266Q, and R263L), indicating that the allosteric site of the epimerase resides in the region of codons 263 to 266 [12,13].…”
Section: Molecular Biologic Aspectsmentioning
confidence: 99%
“…A nonlysosomal disorder that will be detected in a screen of sialic acid content is sialuria. 29 This is a relatively mild disorder that results from the excessive synthesis of sialic acid due to the lack of feedback inhibition at the UDP-N-acetyl-glucosamine-2-epimerase step. Recent studies have demonstrated that this disease could be inherited as a dominant trait.…”
Section: Lysosomal Disorders: Diagnosis and Treatmentmentioning
confidence: 99%